Surgical excision of symptomatic nonunions of the fifth metatarsal base fractures: A systematic review of outcomes and complications - Zack Hill, DPM, AACFAS; Ceclina Cao, PMS-3; Patcharathorn Pookun, PMS-2; Fely Jhae D. Ebanculla, PMS-2; Guanjin Chen, PMS-3 (Foot & Ankle Surgery: Techniques, Reports & Cases, 2025)
Background: Symptomatic non-unions of the fifth metatarsal base, particularly in Zones 1 and 2, pose significant treatment challenges. Surgical management includes open reduction internal fixation (ORIF) or excision of the non-union fragment. Though less technically demanding, excision procedures risk disrupting important tendon and ligamentous attachments, potentially affecting foot function. Methods: This review synthesizes available data on surgical excision as a definitive treatment, addressing outcomes and complications. A systematic review of PubMed, Embase, Cochrane Library, and Google Scholar was performed to identify studies reporting on the excision of nonunion fragments at the proximal fifth metatarsal. Inclusion criteria required studies to present functional outcomes and complications following excision in Zones 1 and 2. Of 156 studies reviewed, 4 met the criteria, encompassing 18 patient cases. Results: All 18 patients underwent excision of the proximal fragment, with various techniques used to preserve peroneal tendon function. Twelve patients were high-level athletes, and all returned to sport without pain or functional limitations. One study reported a significant improvement in AOFAS forefoot scores (from 58.6 to 95; p = 0.024) and VAS scores (from 8.0 to 1.6; p = 0.023). At an average follow-up of 18.3 months, 100 % of patients were pain-free, and no complications were reported. Conclusion: Excision of symptomatic non-unions of the fifth metatarsal base, particularly in Zone 1 and selective cases for Zone 2, appears to be a safe and effective treatment option, allowing for significant pain relief and return to activity in high-level athletes. Further research is needed to validate long-term outcomes and optimal surgical techniques.